2019
DOI: 10.1007/s11420-018-9634-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Fiber-Reinforced Polymer Intramedullary Nails Perform Poorly in Long-Bone Surgery

Abstract: Background: Carbon-fiber-reinforced (CFR) polymer has produced great excitement in the orthopedic community as a material that will reduce bone healing times and provide improved image quality. Osteotomy stabilized with an intramedullary (IM) nail has become a common technique to address post-traumatic malalignment of the lower extremity. Purposes/Questions: The following questions were asked: (1) Did CFR polymer nails provide a rapid healing time after long bone osteotomy, shortening, or fracture? (2) Did the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…10 However, previous studies reported mixed results regarding the fatigue strength and durability of CF implants. 16,17,21 Although CF nails may have reduced risks of fatigue failure, some nails still failed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 However, previous studies reported mixed results regarding the fatigue strength and durability of CF implants. 16,17,21 Although CF nails may have reduced risks of fatigue failure, some nails still failed.…”
Section: Discussionmentioning
confidence: 99%
“…Still, previous studies report mixed results with relatively high nonunion rates in a single center using 16 CF nails for diaphyseal correction osteotomy (11 limbs), shortening surgery (3 limbs), and diaphyseal closed tibial fractures (2 limbs), and low nonunion rates in a multicenter study with 96 oncologic patients treated with CF plates. 21,22 Besides, a single-institutional study in 2017 investigated 53 CF nails in oncologic patients of which one nail developed a stress fracture proximally to the distal static screw, and a more recent single-institutional case-control study (with 36 titanium nails and 36 CF nails) demonstrated no differences between both groups regarding operating time, surgical wound infection, and survival. 35,36 Our findings, together with the above studies, highlight an acceptable mechanical failure rate in the oncologic population, which has also been reported for titanium nails (Supplementary Table II, http://links.lww.com/JAAOS/A954).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal artifact reduction sequence MRI and carbon fiber nails can be used to circumvent this issue 21 . Although carbon fiber nails enable more effective RT and reduction of artifact on surveillance imaging, early reports of failure suggest inferior biomechanical properties [22][23][24][25] .…”
Section: Treatment Options Prophylactic Fixationmentioning
confidence: 99%